Hydroxypropyl Cellulose Adhesives for Transfer Printing of Carbon Nanotubes and Metallic Nanostructures. Issue 47 (1st November 2020) - Dore, Camilla; Dörling, Bernhard; Garcia‐Pomar, Juan Luis; Campoy‐Quiles, Mariano; Mihi, Agustín
Abstract: Transfer printing is one of the key nanofabrication techniques for the large‐scale manufacturing of complex device architectures. It provides a cost‐effective and high‐throughput route for the integration of independently processed materials into spatially tailored architectures. Furthermore, this method enables the fabrication of flexible and curvilinear devices, paving the way for the fabrication of a new generation of technologies for optics, electronics, and biomedicine. In this work, hydroxypropyl cellulose (HPC) membranes are used as water soluble adhesives for transfer printing processes with improved performance and versatility compared to conventional silicone alternatives. The high‐water solubility and excellent mechanical properties of HPC facilitate transfer printing with high yield for both metal and carbon nanotubes (CNTs) inks. In the case of metal inks, crack‐free stripping of silver films and the simple fabrication of Moiré Plasmonic architectures of different geometries are demonstrated. Furthermore, HPC membranes are used to transfer print carbon nanotube films with different thicknesses and up to 77% transparency in the visible and near infrared region with potential applications as transparent conductive substrates. Finally, the use of prepatterned HPC membranes enables nanoscale patterning of CNT with feature resolution down to 1 µ m. Abstract : Water soluble hydroxypropyl cellulose (HPC) membranes are presented as biocompatible adhesives for transfer printing of carbon nanotubes and metal nanopatterns. The nanofabrication possibilities offered by HPC are illustrated by the crack‐free stripping of silver films and the simple fabrication of Moiré plasmonic architectures. In the case of carbon nanotubes, different thicknesses and patterns down to 1 µm are demonstrated.